Sarcophaginae (Diptera: Sarcophagidae) da Amazônia Brasileira - SOUZA, Matheus Tavares de (Universidade Federal do Pará, 2023)
The family Sarcophagidae (Diptera) has a cosmopolitan distribution, comprising 3.000 describeds species in 355 genera. Sarcophaginae is the most abundant and diverse subfamily in the new world. There are few studies about the family from Neotropical region, especially from Brazilian Amazon region, where there are few taxonomists. Therefore, this study enlarge the knowledge on the fauna of Sarcophaginae from the Brazilian Amazon, through descriptions and redescriptions of species and confection of dichotomous key to species of this region. This work was based on bibliographic survey and specimens from Brazilian Amazon housed in four entomological collections of Brazil. Morphological analysis, measurements and drawings of male species was presented. 132 species and 31 genera of Sarcophaginae from Brazilian Amazon have been found. Was made a description of a two new specie of the genus Dexosarcophaga and one Rettenmeyerina . A redescription of the monotypic genus Promayoa Dodge, 1966, was made with new illustrates. A keys to males are also provided, except for the species of the genus Lepidodexia , because the large number of undescribed Neotropical species of this genus would make any effort premature pending a complete revision of the fauna.